The Negative Factors that Influence the Performance of Ghanaian Construction Projects - Benjamin Boahene Akomah; Prasanna Venkatesan Ramani (Construction Economics and Building)
Numerous factors affect the performance of construction projects. The goal of this paper is twofold: first, to identify and determine the negative factors influencing construction projects, and second, to specify the hypothesised causal relations between the observed and hidden variables using a confirmatory factor analysis (CFA) model. A deductive research approach and a cross-sectional design method were chosen for the study. A literature review was first conducted, and 66 negative variables were identified. The factors were modified and designed into a questionnaire for data collection. The Cronbach alphas of the three components indicate a high degree of internal consistency. The measurement variables adequately measure the negative factor construct. In addition, the fit indices suggest that the postulated model sufficiently describes the dataset. Poor environmental practices (PAS2), inadequate environmental legislative framework to address modern environmental concerns in the delivery of construction projects (PAS1), and non-inclusion of occupational health and safety in contracts (PAS3) were identified as three relevant negative factors impacting project performance. The paper identified poor assessment strategies, weak management systems, and inefficient regulatory systems as the significant latent factors that affect performance. According to the findings, a poor assessment strategy is more consequential. The results of the study suggest that poor assessment strategies, weak management systems, and inefficient regulatory systems can lead to worsening health and safety conditions in the construction industry, as well as environmental violations and poor environmental practices. The government should enact adequate health and safety and environmental and local community protection laws to protect the environment and local communities during construction. Clients must liaise with consultants to incorporate sufficient health and safety clauses into construction contracts and ensure judicious compliance by contractors. To reduce corruption in the construction sector, the government should strengthen its anti-corruption mechanisms.